Pengelolaan Bank Sampah “Sampat Sehe Kedas” Desa Selat, Kecamatan Sukasada, Kabupaten Buleleng - Wirawan, Putu Angga; Tripalupi, Lulup Endah (Universitas Pendidikan Ganesha, 2021)
The purpose of this study was to determine the management of the “Sampat Sehe Kedas” Waste Bank in Selat Village, Sukasada District, Buleleng Regency. This research uses qualitative research methods. Data collection techniques using interview and documentation methods. The determination of informants was done purposively. The data obtained from the interviews were analyzed by producing, presenting, and drawing conclusions. The results of the research on the Management of the Sampat Sehe Kedas Waste Bank in Selat Village show that planning is going well in terms of goal setting, namely wanting to help the community in managing waste by forming an organization, providing a financial budget, fulfilling equipment and equipment, identifying problems, and developing plans by deliberation. Organizing goes well in terms of the formation of the organizational structure. The briefing went well, seen from the coordination between the chairman and officers before carrying out activities and giving each other motivation. Supervision runs well, seen from the standard of implementation, the management and officers have worked according to the agreed day and the waste that customers save is non-organic waste at a price of Rp. 500.00/ kg